An analysis of the taxation effects and considerations for multinational entities with dual residency issues, from a South African perspective - Weideman, Nicolette (My University, 2016)
There has been significant advances in the international arena with regards to global economic growth and trade, as well as enormous competition by countries to attract inward foreign direct investment from multinational enterprises (MNEs) to ensure the sustainability of their own economies. Fundamentally the contentious issue is the possibility of double taxation (DT), due to the dual residency of the MNE. The MNE operates in various markets which results in cross-border transactions, whether physical or electronic, and this ultimately means that different tax jurisdictions will become applicable and enforceable by each relevant country. These dual resident MNEs could be seen as a tax resident in both countries and thus be liable for tax obligations in both of these countries. This would therefore lead to the same income incurring DT or double non-taxation (DNT), which would have a devastating impact on that MNE. This lead to the establishment of double taxation treaties, agreements and conventions (DTA’s), between various countries which are aimed at addressing this imbalance. As technology advances at an alarming rate, so too does the possibility of abuse of tax treaties. Two important criteria are ‘the place of effective management’ (POEM) and the ‘permanent establishment’ (PE), which are critical to the determination of the correct tax jurisdiction where the dual resident MNE will incur various tax liabilities. These concepts, POEM and PE, can be confusing but are imperative, in order to prevent DT, and which could prejudice the relevant fiscus, as well as an attempt to avoid any conflict between the taxing regimes. An interesting facet of the POEM and PE conundrum is the interpretation by the Organisation for Economic Co-operation and Development’s (’the OECD’) Model Tax Convention (MTC) compared to the interpretations by the South African Revenue Service (SARS). Another area of contention for MNEs is the current enormous global focus on the concept of Base Erosion and Profit Shifting (BEPS), which is under great scrutiny, and is of great concern for the majority of revenue authorities. These authorities are intensifying their focus on improving and enforcing anti-avoidance provisions to prevent taxation leakage in their respective tax jurisdictions. This shift in priorities opposes one of a MNE’s main business objectives which is to maximize profits, by either diverting, extracting and/or distributing profits out of a high tax paying jurisdiction into a lower tax paying jurisdiction. This will consequently create an additional business risk which emphasises the need for international tax expertise. The international tax expert is a valuable business team member, as their knowledge and expertise is imperative for the mitigation of possible tax risks, correct interpretation and application of the relevant tax legislation on the business flows of the MNEs as a result of operational expansion or any cross-border transactions or activities. Key Words: Taxation, Tax Treaties, Agreements, BEPS, Conventions; Cross-border, Double Taxation; Dual Residency; International tax, Multinational enterprises; Permanent Establishment, Place of Effective Management; OECD Model Tax Convention; Tax Intelligence, Tax Jurisdictions
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation).
Keywords: Taxation; Tax treaties; Agreements; Double taxation; Dual residency; International tax; Multinational enterprises; Permanent establishment; OECD Model Tax Convention